2010
DOI: 10.1088/0004-637x/717/1/597
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Activity-Related Meridional Flow Modulation on the Strength of the Solar Polar Magnetic Field

Abstract: We studied the effect of the perturbation of the meridional flow in the activity belts detected by local helioseismology on the development and strength of the surface magnetic field at the polar caps. We carried out simulations of synthetic solar cycles with a flux transport model, which follows the cyclic evolution of the surface field determined by flux emergence and advective transport by nearsurface flows. In each hemisphere, an axisymmetric band of latitudinal flows converging towards the central latitud… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
74
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 33 publications
3
74
0
Order By: Relevance
“…Sun et al (2015) found an anti-correlation between active region field strength and the mid-latitude poleward flow speed of the associated decayed field, consistent with a fielddependent converging flow towards active regions (Zhao and Kosovichev, 2004). Using a fluxtransport model, Jiang et al (2010) studied the effect of meridional flow perturbations caused by near-surface inflows towards the active region band in each hemisphere, and found that large perturbations reduce the tilt angles of bipoles, thus reducing their contribution to the polar field changes. The amplitude of the meridional flow perturbations are larger for stronger solar cycles, consistent with the anti-correlation between Joy's law tilt and cycle amplitude reported by Dasi-Espuig et al (2010).…”
Section: Unusual Cycle 23 Minimummentioning
confidence: 86%
“…Sun et al (2015) found an anti-correlation between active region field strength and the mid-latitude poleward flow speed of the associated decayed field, consistent with a fielddependent converging flow towards active regions (Zhao and Kosovichev, 2004). Using a fluxtransport model, Jiang et al (2010) studied the effect of meridional flow perturbations caused by near-surface inflows towards the active region band in each hemisphere, and found that large perturbations reduce the tilt angles of bipoles, thus reducing their contribution to the polar field changes. The amplitude of the meridional flow perturbations are larger for stronger solar cycles, consistent with the anti-correlation between Joy's law tilt and cycle amplitude reported by Dasi-Espuig et al (2010).…”
Section: Unusual Cycle 23 Minimummentioning
confidence: 86%
“…a stronger cycle produces a smaller tilt angle and therefore a weaker poloidal seed field for the n+1 cycle (Cameron and Schüssler, 2012). Jiang et al (2010) study the effect of meridional flow perturbations and find that larger perturbations reduce the tilt angle of bipolar magnetic regions and thus diminish its contribution to the polar field. The perturbations are caused by near-surface inflows towards the active region band in each hemisphere, and the perturbation amplitude increases with stronger magnetic cycles.…”
Section: Discussionmentioning
confidence: 99%
“…At this point the inflows are so weak that the subsequent evolution of the BMR is dominated by the differential rotation and the random walk. It should be noted that inflows restrict the growth of the latitudinal separation of polarities over time rather than reducing it (see Jiang et al 2010). The decrease in B p is a consequence of how the latitudinal separation and the enhanced flux destruction balance.…”
Section: Dependence Upon Initial Tiltmentioning
confidence: 99%
“…They found that, even for comparatively weak inflows, the inflows cause the magnetic concentrations to clump together and generate patterns that are inconsistent with observations. Jiang et al (2010) included a magnetic-field-dependent, axisymmetric latitudinal perturbation of the meridional flow compatible with the inflows in SFT simulations and found that this reduced the latitudinal separation of the polarities of the emerged BMRs, thus limiting the buildup of magnetic field at the polar caps. Cameron & Schüssler (2012) argue that this effect dominates in strong cycles, while in weak cycles the perturbation of the meridional flow enhances crossequatorial flux transport and accelerates the reversal of the polar fields.…”
Section: Introductionmentioning
confidence: 99%